2003
DOI: 10.1038/sj.npp.1300037
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Morphine Preference Following Prolonged Abstinence: Association with Increased Fos Expression in the Extended Amygdala

Abstract: We previously found that chronically morphine-pretreated, abstinent rats show stronger preferences for morphine-associated environments than placebo-pretreated rats. Here we show that this increased preference persisted for at least 5 weeks after withdrawal of chronic morphine. To determine brain regions involved in this behavior, we examined neural activation (as indexed by Fos-like proteins) induced by a morphine-conditioned place preference test. Placebo-pretreated (P) morphine-conditioned rats showed signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
45
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(56 citation statements)
references
References 53 publications
10
45
1
Order By: Relevance
“…The finding that Fos expression in Cg and BLA showed significant positive correlations with preference scores in both abstinent and placebo-pretreated conditioned groups is consistent with what we previously reported for morphine place preference conditioning [23]. Thus, our current and previous results indicate that the Cg and BLA are associated with the expression of the positive reinforcing aspects of both food and drugs.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The finding that Fos expression in Cg and BLA showed significant positive correlations with preference scores in both abstinent and placebo-pretreated conditioned groups is consistent with what we previously reported for morphine place preference conditioning [23]. Thus, our current and previous results indicate that the Cg and BLA are associated with the expression of the positive reinforcing aspects of both food and drugs.…”
Section: Discussionsupporting
confidence: 92%
“…Previously we found that elevated Fos levels in the VL-BNST of morphine withdrawn animals were positively correlated with enhanced morphine preference [27], whereas in the present study elevated Fos levels in the VL-BNST were negatively correlated with food preference. Thus, the BNST may be a site where aversive responses to environmental stressors help to drive drug seeking behavior that can alleviate stress while decreasing the desire for natural rewards that are not effective in alleviating stress.…”
Section: Discussioncontrasting
confidence: 84%
See 2 more Smart Citations
“…The latter finding suggests that c-Fos expression was activated by the presentation of alcohol-paired stimuli and not by the performance of operant behavior. Our observation of increased c-Fos expression in the BLA after reexposure to the alcoholpaired discrete cues is in agreement with earlier studies which showed that reexposure to cocaine-, amphetamine-, morphine-, or beer-associated context and discrete cues activated c-Fos in this brain region (Topple et al, 1998;Baker et al, 1999;Mead et al, 1999;Neisewander et al, 2000;Ciccocioppo et al, 2001;Harris and Aston-Jones, 2003). Moreover, the BLA has been shown to be involved in context-and cue-induced relapse to drug-seeking, and to control the ability of environmental stimuli to form Pavlovian associations with reinforcing stimuli (Whitelaw et al, 1996;Meil and See, 1997;Kruzich and See, 2001;Shalev et al, 2003).…”
Section: Pattern Of C-fos Activation In the Amygdala: A Role In Plastsupporting
confidence: 93%